How both positive and burdensome caregiver experiences are associated with care recipient cognitive performance: Evidence from the National Health and Aging Trends Study and National Study of Caregiving - Alexandra M. Wennberg; Loretta R. Anderson; Annachiara Cagnin; Lenis P. Chen-Edinboro; Lorenzo Pini (Frontiers Media S.A., 2023)
IntroductionBeing an informal caregiver to a person with chronic disease, including persons living with dementia (PLWD), is a big role to take on and many caregivers experience both substantial burden and emotional reward related to caregiving. Care recipient factors (e.g., behavioral symptoms) are associated with caregiver experience. However, the relationship between caregiver and care recipient is bidirectional, so it is likely that caregiver factors impact the care recipient, though few studies have investigated this.MethodsIn the 2017 round of the National Health and Aging Trends Study (NHATS) and National Study of Caregiving (NSOC), we studied 1,210 care dyads-−170 PLWD dyads and 1,040 without dementia dyads. Care recipients completed immediate and delayed word list memory tasks, the Clock Drawing Test, and a self-rated memory rating, while caregivers were interviewed about their caregiving experiences using a 34-item questionnaire. Using principal component analysis, we created a caregiver experience score with three components-Practical Care Burden, Positive Care Experiences, and Emotional Care Burden. We then investigated the cross-sectional association between caregiver experience components and care recipient cognitive test performance using linear regression models adjusted for age, sex, education, race, and depressive and anxiety symptoms.ResultsAmong PLWD dyads, a higher caregiver Positive Care Experiences score was associated with better care recipient performance on the delayed word recall (B = 0.20, 95% CI 0.05, 0.36) and Clock Draw (B = 0.12, 95% CI 0.01, 0.24) tests while higher Emotional Care Burden score was associated with worse self-rated memory score (B = −0.19, 95% CI −0.39, −0.003). Among participants without dementia, higher Practical Care Burden score was associated with poorer care recipient performance on the immediate (B = −0.07, 95% CI −0.12, −0.01) and delayed (B = −0.10, 95% CI −0.16, −0.05) word recall tests.DiscussionThese findings support the concept that caregiving is bidirectional within the dyad and that positive variables can positively impact both members of the dyad. This suggests that caregiving interventions should target the caregiver and recipient both individually and as a unit, with the goal of holistically improving outcomes for both.